Transcanal endoscopic type 1 tympanoplasty in children: Cartilage butterfly and fascia temporalis graft. (June 2019) - Bartel, R.; Levorato, M.; Adroher, M.; Cardelus, S.; Diaz, A.; Lacima, J.; Vazquez, C.; Veneri, A.; Wienberg, P.; Claveria, M.A.; Haag, O.H.
Abstract: Introduction: Endoscopic type 1 tympanoplasty is every day gaining numerous adepts for tympanic membrane repair. Due to the value of reducing postauricular approaches, decreasing postoperative morbidity and hospitalization time. The objective of this study is to present surgical results of endoscopic type 1 tympanoplasty in the pediatric population using fascia temporalis or cartilage butterfly graft. Materials and methods: Prospective study regarding the pediatric population, mean age of 10.7 years old. Patients diagnosed with chronic otitis media without cholesteatoma and intact ossicular chain. Tympanic membrane reconstruction using inlay cartilage butterfly graft or underlay fascia temporalis graft according to surgical needs. Audiograms were evaluated preoperatively and 6 months after surgery. No postauricular approaches were performed. Results: A total of 54 ears were operated, 25 utilizing underlay fascia temporalis graft and 29 using inlay cartilage butterfly graft. Six months following surgery, dry and closed tympanic membranes were obtained in 54 cases (92.6%). Preoperative and postoperative air conduction (AC) thresholds, bone conduction (BC) thresholds and air-bone gaps (ABG) were assessed. Preoperative AC of 24.6 dB, BC of 8.9 dB and an ABG of 15.5 dB. Postoperative AC of 16.3 dB, BC of 8.9 and an ABG of 6.9 dB. A postoperative ABG reduction of 8.5 dB was reached. Conclusion: Transcanal endoscopic type 1 tympanoplasty can be achieved in every pediatric patient with chronic otitis media without cholesteatoma, and, is a safe and efficient procedure.